Tinjauan Kesesuaian Data Navgate Terkait Q-Code untuk Pembuatan Notice to Airmen (NOTAM) di NOTAM Office Indonesia - Putri, Melisa Dwi; Sadiatmi, Rini; Praptiningsih, Nunuk (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
Errors in the use of Q-Code in NOTAM publication can lead to miscommunication of information, which may negatively impact flight safety and operational efficiency. This study aims to analyze the factors causing Q-Code errors in NOTAM issued by the Notam Office Indonesia and to evaluate the impact and solutions to these problems. The research applies a qualitative approach through interviews with AIS personnel at the Notam Office Indonesia and an analysis of NOTAM documents that indicate potential Q-Code errors. . The findings show that the errors occur due to several factors, including limitations in the Q-Code reference within the Navgate application and incomplete or unclear raw data submissions from NOTAM originators. These errors result in stakeholder misinterpretation, disruptions to flight operations, and a decline in NOTAM data quality. As a form of mitigation, it is recommended to update the Q- Code database in Navgate and strengthen coordination between NOTAM proposing units and the Notam Office Indonesia. With these improvements, the overall quality of NOTAM can be enhanced to better support aviation safety.